Actual Aspects of Sepsis - K. P. Gruver; V. B. Beloborodov; T. N. Kuzmenko (Антибиотики и Химиотерапия, 2020)
Cases of sepsis with bacteriemia detected in the S.P. Botkin State Clinical Hospital within 2000-2007 were analysed. The sources of the bacteriemia, the etiological pattern of the pathogens and their susceptibility to antibacterials were estimated. The study enrolled 256 patients with sepsis. The antibiotic susceptibility of 227 isolates from the blood samples was tested. More than a half of the infection sources was detected in the organs of the respiratory tract and abdominal cavity. All the grampositive pathogens were susceptible to vancomycin and linesolid. The overwhelming majority of the enterococcal isolates proved to be susceptible to carbapenem and cefepim.